A teoria da objetivação na formação inicial: um diferencial para as práticas educativas - RABELO, Neliane Mota (Universidade Federal do Oeste do Pará, 2025)
The aim of this thesis is to discuss, based on the assumptions of Objectivation Theory (OT), how educational practices are developed that enable the use of Digital Information and Communication Technologies (DICTs) to be enhanced, with a view to critical and reflective use in initial teacher training, through educational practices developed with the co-producers, students on the Integrated Degree Course in Mathematics and Physics – LIMF, at UFOPA, Santarém campus. The research discussed the foundations of OT, based on Radford, initial teacher training and the use of ICT. The research method was based on the assumptions of dialectical materialism and multimodal research. Four formative moments were produced, through which the collective production of knowledge was sought through the planning, production and realization of the Teaching-Learning Activity – TLA. During the first training session, Google Forms was used to draw up an initial profile of the participants and, at the end of each training session, a report on the activities carried out. A bibliographic survey was carried out to narrow down our research object. The research presents four formative moments and nine meetings aimed at achieving the proposed objectives, seeking the relationship between the technological artifacts, the TDIC, through the use of the cell phone and the Geogebra software as an integral part of the formative process of the AEA carried out, aiming at the collective work of the co-producers in the act of carrying out the AEA within the Pedagogical Residency Program - PRP. The results indicate that, through the formative moments and meetings held, the co-producers, through the planning, production and realization of the AEA developed collectively, contribute to more conscious, critical and non-alienating educational practices regarding the use of ICT. From the results presented in the research, it can be concluded that OT can be an enabler of educational practices in initial training, contributing to the training of ethical and critical professionals in the use of resources and in the teaching-learning process in a collective way. Through TO, the co-producers developed a critical and reflective vision, through which they learned to value the cultural and social dimension of the educational process, recognizing that knowledge is not just an abstraction, but something rooted in the students' cultural and historical experiences, which we consider a crucial point for future teachers who will work in the Amazon.
Keywords: Formação Inicial; Práticas Educativas; Teoria da Objetivação; CNPQ:: CIÊNCIAS HUMANAS